Photothermoacoustic effect: applied aspects of stressed state area diagnostics in structural materials - Alekseev, A.N.; Burbelo, R.M.; Zhabitenko, N.K.; Kuz‘mich, A.G. (Functional Materials, 2004)
Specific features of photothermoacoustic (PTA) transformation process in materials under stress have been studied in experiment and theoretically. Pulse and harmonic modulation regimen of laser emission have been considered. Basing on the results so obtained, a circuit design has been proposed for the stressed area PTA diagnostics in structural materials. Экспериментально и теоретически исследованы особенности процесса фототермоакустического (ФТА) преобразования в напряженных материалах. Рассмотрены импульсный и гармонический режимы модуляции лазерного излучения. На основании полученных результатов предложена функциональная схема ФТА диагностики напряженных областей в конструкционных материалах. Проведено експериментальні та тєорєтичні дослідження особливостей процесу фото-термоакустичного (ФТА) перетворення у напруженому середовищі у випадку імпульсного та гармонічного режимів модуляції лазерного випромінювання. На основі отриманих результатів запропоновано функціональну схему ФТА діагностики областей напруженого стану в конструкційних матеріалах.